Faktor-faktor yang mempengaruhi pelaksanaan audit bangunan di institut latihan awam - Awang, Norhayati (2020)
Asset is an invaluable property to all levels of community. Asset or building ownership to an organisation has the capability of delivering the best services to its customers. Every public building or government premise has to be managed efficiently and effectively so that it is able to delivery satisfactory services to customers in achieving the aim of the organisation. A good asset management would depend on the implementation of facility management on the particular asset. An organisation must conduct a systematic planning in managing the asset and facility effectively to ensure users and customers security. In order to succeed in the management of asset and facility in Public Training Institutions (ILA), several guidelines have been issued by related agencies namely DPAK and TPATA which are the basic/fundamental source of reference and guide in ensuring the best maintenance level for the existing buildings and facilities. Public Works Department (JKR) too has issued Garis Panduan Pemeriksaan dan Penilaian Keadaan Bangunan Sedia ada which could be used in conducting examination on a building. Nonetheless, the awareness on the implementation of building audit has yet to reach an expected level which led to the occurrence of undesired incidents such as fire breakouts and others. Therefore, the study conducted in identifying the factors that influence audit implementation in ILA is hoped to assist these institutions and the relevant quarters in improving the current situation and subsequently avoid uncalled situation from occurring. Four groups of respondents are interviewed namely INSPEN, INTAN, ILKAP dan JKR, in identifying the factors that influence audit implementation in ILA. The study findings have identified 13 main factors that contributed to the situation. Further analysis using priority index shows that the three main factors that contributed to this scenario and highly influential on the level of building audit implementation are the commitment of the management, finance and effective record management.